Isolation and molecular characteristics of D2 genotype of Aichivirus D in dairy cattle in China - Yan, Nan; Xu, Dongping; Yue, Hua; Tang, Cheng (Frontiers in Veterinary Science, 2025)
Aichivirus D (AiV-D), a newly emerging member of the Kobuvirus genus, is associated with diarrhea in cattle. This study aimed to investigate the prevalence and molecular characteristics of AiV-D among dairy cattle in China. From October 2021 to August 2022, 279 fecal samples were collected from diarrheal dairy cattle across seven provinces in China. Among these, 37 samples (13.2%) tested positive for AiV-D by RT-PCR, indicating a wide geographical distribution of AiV-D in Chinese dairy cattle. Phylogenetic analysis based on the complete VP1 gene revealed that Chinese dairy cattle AiV-D strains belong to the AiV-D2 genotype, with unique amino acid changes in VP0, VP3, and VP1 that distinguish them from known AiV-D strains. Additionally, an AiV-D strain was successfully isolated, and its complete genome was sequenced. Phylogenetic analysis of the complete genome and individual genes confirmed the strain’s classification within the AiV-D2 genotype. This study reports the first detection of the AiV-D2 genotype outside Japan, highlighting the need for future surveillance to better understand the epidemiology and diversity of AiV-D in China.